Performance analysis of circular polarization X-band microstrip patch antenna combined with conical horn - B. Pratiknyo Adi Mahatmanto; Dedi Irawadi; Hidayat Gunawan; Nugroho Widi Jatmiko; Dinari Nikken Sulastrie Sirin; Supriyono Supriyono; Suhermanto Suhermanto; Bambang Dewandaru; Catur Apriono (Universitas Ahmad Dahlan, 2024)
A ground station antenna system features a conical horn attached to a microstrip antenna as an alternate receiving feed antenna. The proposed microstrip antenna has circular polarization and operates in the X-band. The far-field parameters of the antenna are measured after developing and simulating the combination of a conical horn and a microstrip antenna. The modeling results for a microstrip antenna with a conical horn offer a working bandwidth of 930 MHz, spanning frequencies 7.44 GHz to 8.37 GHz. The axial ratio measurements for a microstrip antenna joined with a conical horn produce a working bandwidth of 150 MHz, covering frequencies ranging from 7.72 GHz to 7.87 GHz. The conical horn is attached to a microstrip antenna and has a gain of 15.1 dB. The proposed antenna is designed to meet ground station antenna requirements by pairing it with a parabolic reflector with a diameter of 3.7 meters. The primary focus antenna of the proposed design was chosen. The feed antenna and parabolic reflector should be positioned at a focus point distance of 1110 mm for a total gain of 38.9 dB at 7.8 GHz frequency. The proposed antenna can be applied on X-band remote sensing ground stations as a receiving antenna.